World religions: a guide to the essentials - Robinson, Thomas A. (Baker Academic, a division of Baker Publishing Group, 2022)
"This masterful survey of world religions, now revised throughout, presents a clear and concise portrait of the history, beliefs, and practices of eastern and western religions"--